STUDENTS’ VOICES ON ONLINE ENGLISH LEARNING - Akhmad Hairul Umam (Pedagogia: Jurnal Ilmiah Pendidikan, 2021)
The research study investigated the students’ voices on online English learning during the Covid-19 pandemic. This study was taken in quantitative and qualitative approach using the questionnaire and interview in which the data were taken through an online with descriptive analysis. The research involved 46 participants who learned online English at higher education in Jakarta. Based on the result data, indicated that respondents who have been learning online English for one semester accepted moderately. Moreover, a few of them argued that online English learning during the Covid-19 as the best alternative to mitigate the spread of viruses in Education cluster. Participants showed big concern with health problem and made it as priority for their life decision in emergency situation of Covid-19 pandemic. Although the implementation of online English learning still has challenges and difficulties for students, they have optimism and slowly accustomed to use technology in language learning and becoming autonomous learning.